In vivo monitoring of remnant undifferentiated neural cells following human induced pluripotent stem cell‐derived neural stem/progenitor cells transplantation. (6th January 2020) - Tanimoto, Yuji; Yamasaki, Tomoteru; Nagoshi, Narihito; Nishiyama, Yuichiro; Nori, Satoshi; Nishimura, Soraya; Iida, Tsuyoshi; Ozaki, Masahiro; Tsuji, Osahiko; Ji, Bin; Aoki, Ichio; Jinzaki, Masahiro; et al.
Abstract: Transplantation of human‐induced pluripotent stem cell‐derived neural stem/progenitor cells (hiPSC‐NS/PCs) is a promising treatment for a variety of neuropathological conditions. Although previous reports have indicated the effectiveness of hiPSC‐NS/PCs transplantation into the injured spinal cord of rodents and nonhuman primates, long‐term observation of hiPSC‐NS/PCs post‐transplantation suggested some "unsafe" differentiation‐resistant properties, resulting in disordered overgrowth. These findings suggest that, even if "safe" NS/PCs are transplanted into the human central nervous system (CNS), the dynamics of cellular differentiation of stem cells should be noninvasively tracked to ensure safety. Positron emission tomography (PET) provides molecular‐functional information and helps to detect specific disease conditions. The current study was conducted to visualize Nestin (an NS/PC marker)‐positive undifferentiated neural cells in the CNS of immune‐deficient (nonobese diabetic‐severe combined immune‐deficient) mice after hiPSC‐NS/PCs transplantation with PET, using 18 kDa translocator protein (TSPO) ligands as labels. TSPO was recently found to be expressed in rodent NS/PCs, and its expression decreased with the progression of neuronal differentiation. We hypothesized that TSPO would also be present in hiPSC‐NS/PCs and expressed strongly in residual immature neural cells after transplantation. The results showed high levels of TSPO expression in immature hiPSC‐NS/PCs‐derived cells, and decreased TSPO expression as neural differentiation progressed in vitro. Furthermore, PET with [ 18 F] FEDAC (a TSPO radioligand) was able to visualize the remnant undifferentiated hiPSC‐NS/PCs‐derived cells consisting of TSPO and Nestin + cells in vivo. These findings suggest that PET with [ 18 F] FEDAC could play a key role in the safe clinical application of CNS repair in regenerative medicine. Abstract : By utilizing the characteristic of neural stem/progenitor cells (NS/PCs) to express translocator protein (TSPO), positron emission tomography (PET) with TSPO ligand was able to visualize residual immature neural cells after NS/PCs transplantation.